Legal Responsibility of the Insurance Company for Unpaid Participant Claims - Polontoh, Herry (Riviera Publishing, 2024)
Insurance is a financial institution that has a vital role in the economy. Insurance protects the public from various risks, such as accidents, illness, and death. The insurance company must pay claims to insurance participants who experience losses in an insurance agreement. However, in practice, claims are often rejected by insurance companies. The purpose of this research is to analyze the legal responsibility of insurance companies for unpaid participant claims. This research uses normative legal research methods. Research data was obtained through a literature study. Research data was analyzed qualitatively using descriptive analysis methods. The research results show that insurance companies that reject insurance participants' claims can be subject to civil and criminal legal responsibility. If the participant's claim is not paid, the participant can file for bankruptcy through court. The regulations that provide the legal umbrella for protecting insurance participants consist of Law Number 8 of 1999 concerning Consumer Protection, Law Number 40 of 2014 concerning Insurance, Decree of the Minister of Finance No. 422/KMK.06/2003 concerning the Implementation of Insurance Business and Reinsurance Companies, and Financial Services Authority Regulation Number 23/POJK.05/2015 concerning Insurance Products and Marketing of Insurance Products. Legal protection for insurance policyholders as consumers are regulated in the Insurance Law and the Consumer Protection Law.